Hysteretic model of Y-type perfobond rib connectors with large number of ribs. (March 2020) - Kim, Dae-Yoon; Gombosuren, Munkhtulga; Han, Oneil; Kim, Sang-Hyo
Abstract: This study analyzes the shear and hysteresis behavior of Y-type perfobond rib shear connector and suggests a hysteretic model. Y-type perfobond rib shear connectors with different number of ribs (4 ribs, 6 ribs, and 8 ribs) are considered to evaluate energy dissipation. The aim of this study is to do estimation on hysteretic behavior for large number of ribs, as the size of large number of ribs makes it difficult to proceed with an experiment. Numerical analysis and experimental study are conducted to compare the shear strength and energy dissipation of the specimens. In the experimental study, monotonic loading test and cyclic loading test are performed to investigate the hysteresis behavior of Y-type perfobond rib shear connectors. Cyclic loading test is performed in accordance with European Convention for Constructional Steelwork (ECCS) reference which is a procedure of test for assessing the behavior of structural elements under cyclic loadings. Numerical analysis is conducted since the authentication of Y-type perfobond rib shear connector should be modelled to find the shear resistance of each specimen. For hysteretic model of Y-type perfobond rib shear connector, Bouc-Wen-Baber-Noori (BWBN) model is adopted. Finally, the BWBN model parameters are predicted for shear connectors with large number of ribs based on the experimental data of shear connectors with small number of ribs. The slip amplitude is separated into small slips (1–4 mm) and large slips (over 4 mm) in order to improve the accuracy of the energy dissipation prediction. Highlights: Higher shear resistance of Y-type perfobond rib shear connectors with increasing number of ribs. Better energy dissipation capacity of Y-type shear connector under cyclic loading with increasing number of ribs. Hysteretic model estimation of Y-type shear connector with large number of ribs based on the models of small shear connector.